Membangun Budaya Akademik Perguruan Tinggi - Khaerudin Kurniawan (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Establishing College Academic Life. The most valuable ownership of a higher education institution is its academic autonomy and culture, which are needed to build up the culture and civilization of the society and the country as a whole. The quality of a college at present and in the future is determined by the quality of its academic members in establishing the academic life through developing literacy as well as empowering the lecturers. This will be reflected in the development of the reading habit and in the spirit of writing articles and publishing them in scientific journals.